Health literacy of the baby boomer generation and the implications for nursing. Issue 19 (26th July 2018) - Harbour, Peta; Grealish, Laurie
Abstract : Aims and objectives: To investigate the health literacy of the baby boomer generation and what this means for nursing care. Background: Nurses are encouraged to tailor information and education to the individual's level of understanding or health literacy but there may be generational differences in health literacy due to historical, social, and economic contexts. The baby boomer generation, people born between 1946 and 1966, are projected to be high users of health services as they age, therefore nurses' understanding of their health literacy characteristics is important. Design: Integrative literature review. Methods: Database and manual searching for articles occurred in July 2017. Four articles met the criteria. Data were extracted and tabulated, and methodological‐quality was assessed. Results: Three categories of relevance emerged from the analysis of study findings: social demographics may predict health literacy, navigation of the health care system is challenging with low health literacy, and mechanisms to translate information into action remain unclear. Conclusions: Although there is limited evidence to guide practice in regard to health literacy for the baby boomer generation, the emergence of the internet may confound nursing assessment of literacy: people from the baby boomer generation may appear to have higher literacy than they actually possess. Relevance to clinical practice: Sociodemographic information may be used for initial screening for health literacy. Creative questions are recommended to overcome possible stigma associated with individual awareness of low literacy. The mechanisms for translating information into action require further investigation.